Quality of Government in Nigeria - Quantitative Analysis and Evaluation - E.O. , Ohwadua; A.R., Akanji (International Journal of Scientific Research and Management (IJSRM), 2023)
Nigeria gained its independence in 1960, and not until 1999, the nation has witnessed a checkered democracy with military incursion in governance in far more years than civilian administration. Therefore, for Nigeria to have witnessed an unbroken democracy since 1999 to date, is a joyful moment in the annals of history of Nigeria as a nation. However, despite the unbroken democracy for over 23 years, it calls to question Section 14(2) (b) of the Constitution of the Federal Republic of Nigeria 1999, which states that the security and welfare of the people shall be the primary purpose of government. This research paper is therefore a comparative quantitative analysis and evaluation based on certain economic indices of the quality of governance of the three successive governments since Nigeria returned to democracy in 1999. We found that the trend of Corruption Perception Index is high and consistent throughout the three administrations of Presidents Obasanjo, Jonathan and Buhari. Furthermore, while Presidents Obasanjo and Jonathan performed relatively well, Buhari’s administration witnessed a nose-dive trend in all the remaining indices putting his administration as the worst performer in terms of the indicators measured.